If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + -2) + 3x = 20 Reorder the terms: 5(-2 + x) + 3x = 20 (-2 * 5 + x * 5) + 3x = 20 (-10 + 5x) + 3x = 20 Combine like terms: 5x + 3x = 8x -10 + 8x = 20 Solving -10 + 8x = 20 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 8x = 20 + 10 Combine like terms: -10 + 10 = 0 0 + 8x = 20 + 10 8x = 20 + 10 Combine like terms: 20 + 10 = 30 8x = 30 Divide each side by '8'. x = 3.75 Simplifying x = 3.75
| x(3+x)(x-1)=(x+4)(1-x) | | n^3-9n^2+26n-39=0 | | 3a*-3c= | | 2y=3x^2-6x-5 | | 2x+7=-41 | | -2.5q+1.9=-11.6-1q | | x^3-x^2=30 | | (x^2+3)*(x^3+1)=0 | | 9n^2-6n+1=12n+8 | | 2x+3x+120=38 | | -5c+-2c= | | 9n^2-14n-7=0 | | 5-14=2y-2 | | x+2yx-y=0 | | 5x^2+2y^2+2x+4xy-4y+3=0 | | 31-4x=3(7x-8) | | x+(x*1.1666)=3.25 | | 45=-2(10-x) | | 9+6d+d^2=0 | | 10.5-12x=15-8x | | 37=2-5y | | 860-x=368 | | 40+30-x=60 | | 4x+-18=6x+12 | | 4(x+3)=3(x+7) | | 73.51-12x=15-8x | | 2x^2+-16x+32=0 | | 24+4x^2=0 | | 4(3+5+2)+3= | | 3x+x^2+x^3=0 | | x^6-sqrt(-1)=0 | | x+(x-1)+(x-2)+(x-3)x=10 |